Magnetic resonance imaging of cystic fibrosis lung disease - Wielpütz, Mark Oliver; Eichinger, Monika; Puderbach, Michael (Journal of thoracic imaging, 2013)
Lung involvement in cystic fibrosis (CF) disease continues to be a major life-limiting factor of this autosomal recessive genetic disorder. Efforts made toward early diagnosis and advances in therapy have led to sustained survival of affected patients, and many are now of adult age. Because imaging provides detailed information on regional distribution of CF lung disease, repetitive imaging is required for severity assessment and therapy monitoring not only in clinical routine but also for interventional trials. Computed tomography has long succeeded chest radiograph because it provides the highest morphologic detail of airway and parenchymal changes. This is inseparably accompanied by an increase in radiation exposure to CF individuals, who are critically susceptible to, and may accumulate, relevant doses during their lifetime. Magnetic resonance imaging (MRI) as an ionizing radiation-free cross-sectional imaging modality is capable of depicting anatomic hallmarks of CF lung disease at lower spatial resolution but with enhanced tissue characterization. Comprehensive functional lung imaging (imaging of respiratory mechanics, ventilation, and lung perfusion) provides valuable additional information that cannot or can hardly be obtained by any other single diagnostic procedure. The present review article strives to present the current state of lung MRI in CF, as well as its future perspectives. Functional MRI of the CF lung is at the threshold of being considered a routine application, which, supporting early diagnosis, may help to further improve the survival of CF patients.
Gesehen am 08.11.2021